Standalone microgrid control using multi-agent system - Borazjani, Pouya (2015)
A review of power systems shows that distribution systems have been changing due to some issues, such as functions of electrical systems, increases in the number of generating equipment and unpredictable behaviour of the distributed energy resources. According to the aforementioned changes, it appears that the centralized controlling approaches like the traditional SCADA system are no longer the best ways to control the future distribution systems; therefore, the de-centralized controlling system by using microgrids is recommended as a good alternative controlling method to guarantee power network stability. In the area of microgrid control, different methods have been proposed, but the multi-agent system (MAS) has attracted much attention. The MAS controls the microgrids through a communication path. In general, a microgrid can operate in two different modes: grid connected and island mode. Although extensive research has been carried out on control of the microgrid in the island mode by the MAS, toth e knowledge of this researcher, no single study exists that consider the security of communication path, and what would happen if a failure or an error occurred in the communication between the MAS and the microgrid. This work proposed a new structure of the MAS to eliminate the consequences of failure in the communication between the MAS and the microgrid, which is a threat to the stability of the microgrid. The aim of this thesis is to develop the MAS to control the critical loads in different situations including failure in the communication between the MAS and the microgrid (emergency condition). Also, to pay more attention to the economic aspects a microgrid is developed by using a battery bank as a storage device. As a matter of fact, this work redesigns the conventional MAS and challenges it with different scenarios to exhibit its weakness and finally compares it with the proposed MAS. Both the conventional MAS and the proposed one are designed in the coding command and the microgrid model is developed in Matlab/Simulink environment. The simulation results indicate that the proposed MAS can have a seamless transition from the grid connected mode to the island mode in all situations even in the event of a communication failure between the MAS and the microgrid.